TRANSVERSE SCATTERING OF RADIO WAVES BY METEOR TRAILS IN PULSED MODE - A. A. Gaydaev (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The aim of this work is to develop a mathematical tool for describing the scattering of radio signals by meteor trails associated with radio wave dispersion taking into account a range of extenuatory factors. Method The study was carried out using mathematical analysis in the application of meteorite radio wave reflection theory. Results The questions of the scattering of radio waves from undercompacted and overcompacted meteor trails, as measured by radio sounding in a continuous pulse mode, are considered separately. The mechanisms that influence the formation of the amplitude of the RF signal reflected from a meteor trail are discussed in detail. The obtained mathematical expressions enable the initial reflected signal amplitudes from undercompacted and overcompacted meteor trails to be evaluated for power capacity in the different operation modes of radio transmitting stations. Conclusion Following from the theory of the scattering of radiowaves by meteor trails, it is shown that the radiolocation calculation method for sounding meteor trails coincides with the existing theory. The results of the study may be useful for further development of transverse meteor wave propagation theory, especially for the theory of amplitude distribution reflection response.The results may also be used to describe transverse scattering of meteorite trails, as well as for radiolocalisation of meteor trails in both modes.